COMPARATIVE ANALYSIS OF RISK AND RETURN IN PT. BANK BRI SYARIAH BEFORE AND AFTER SPIN OFF - siti ratna sari; darwis harahap; azwar hamid; rahmat annam (Institut Agama Islam Negeri Padangsidimpuan, 2020)
PT. Bank BRI Syariah is one of the banks that performs a spin-off with the aim of making a profit. Researchers use the FDR ratio to assess risk and ROA ratio to assess return at PT. BRI Syariah Bank before and after the spin off. The value of the FDR ratio before and after the spin off fluctuated but net income continued to increase as well as the value of the ROA ratio before and after the spin off fluctuated while net income continued to increase from year to year. The formulation of the problem in this study is whether there are differences in risk and return at PT. BRI Syariah Bank before and after the spin off. The purpose of this study was to analyze the difference in risk and return before and after the spin off. This research is a quantitative research. The data collection technique used is literature study and documentation, through the official website of PT. BRI Syariah, namely www.brisyariah.co.id and the Financial Services Authority, namely www.ojk.go.id. The data analysis technique used descriptive analysis, normality test, sample paired t-test. The data processing process using a computer program, namely SPSS version 22.0. The statistical test results of the paired t-test sample indicate that there are differences in risk (risk) of PT. BRI Syariah Bank before and after the spin off if measured using the Financing to Deposit Ratio (FDR), with a tcount value of 5.288 and a ttable value of 1.70329 (5.288 1.70329). The results of the statistical test of the paired t-test showed that there were differences in the return of PT. BRI Syariah Bank before and after the spin off if measured using Return On Assets (ROA), with a tcount value of 15.318 and a ttable value of 1.70329 (15.318 1.70329).